Principles of classification of complex sentences in Korean. (Journal of Oriental Studies, 2016)
Until now there is no single view on the terminology and classification of a complex sentence among researchers ofKorean. Syntax issues are not fully showed in existing textbooks of Korean language and require in-depth research. This work is devoted to the analysis of the existing classifications of complex sentence of Korean, as well as identifying the principles of their classification.
Keywords: Korean language; syntactic construction; polypredicative construction; syntactic connection tools; syntax of Korean language